The Used of Certificate of Land Rights on Proving in Land Disputes - Enny Agustina (Administrative and Environmental Law Review, 2021)
Based on Article 19 Paragraph (2) of Law No. 5 of 1960 and Article 32 of Government Regulation No. 24 of 1997, it is stated that in land registration, land certificates function as strong evidence. Whether a certificate can only prove property rights, and that evidence is in the judicial process so far. A literature study is conducted to obtain answers by exploring, discussing, and analyzing laws, research reports, and related expert views. The findings indicate that the National Land Agency issued the title certificate during the registration process. If there is a land without a certificate, it can be proven through witness testimony, prediction, confession and oath. A certificate with reliable and complete evidentiary power can only be accepted if there is no claim before the court. A claim against a certificate can be filed if there is a deficiency in its issuance.